2015
DOI: 10.4238/2015.november.18.35
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of microsatellite loci in hybrid giant tiger grouper

Abstract: ABSTRACT. The hybrid giant tiger grouper is a fish that has considerable commercial value and has become increasingly important for aquaculture in South East Asia since 2008. In order to prevent any reduction in genetic diversity in hybrid grouper as a result of aquaculture, we have identified 21 microsatellite markers that can be used to estimate genetic variation in the fish population. The number of alleles at polymorphic microsatellite loci ranged from 2 to 7, and observed and expected heterozygosities var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…A total of 100 SSR primers were designed for PCR amplification and the results showed that 28 primer pairs could successfully amplify the polymorphic fragments. The polymorphic percentage was 28%, which was lower than Ichthyoelephas longirostris (60%) (Landinez-Garcia RM, 2016) Lateolabrax japonicus (42%) (Li BB, 2016) and Geophagus brasiliensishigh (36%) (Ferreira DG, 2013), but higher than Clarias batrachus (17%) [18], hybrid giant tiger grouper (20%) (Huang YS, 2015) and Girella elevate (22%) (McWilliam RA, 2016).…”
Section: Development Of Polymorphic Microsatellite Markersmentioning
confidence: 99%
“…A total of 100 SSR primers were designed for PCR amplification and the results showed that 28 primer pairs could successfully amplify the polymorphic fragments. The polymorphic percentage was 28%, which was lower than Ichthyoelephas longirostris (60%) (Landinez-Garcia RM, 2016) Lateolabrax japonicus (42%) (Li BB, 2016) and Geophagus brasiliensishigh (36%) (Ferreira DG, 2013), but higher than Clarias batrachus (17%) [18], hybrid giant tiger grouper (20%) (Huang YS, 2015) and Girella elevate (22%) (McWilliam RA, 2016).…”
Section: Development Of Polymorphic Microsatellite Markersmentioning
confidence: 99%